Developments in Icelandic Security Policy - Bailes, Alyson J.K., 1949-; Kristmundur Þór Ólafsson 1981- (2014)
Almennar greinar Iceland has been slow in developing a national security concept, for reasons that include a long period of reliance on US protection post-World War Two, and divided internal views over this defence solution. Since the withdrawal of all US stationed forces in 2006, Iceland’s security partnerships have diversified and attempts have been made to frame security in more multi-functional terms. The Risk Assessment Report of 2009 made important progress in itemizing non-military threats and risks. On this basis, a cross-party parliamentary committee was invited to start work in 2012 on guidelines for a security strategy. Its report, published in March 2014, establishes a large area of consensus on ‘softer’ security issues and on remaining in NATO, with a few dissenting voices on the latter. Its main omission is a proper treatment of economic and financial security, still tied to the divisive issue of EU membership. Meanwhile, Iceland’s recent security experience in 2014 has helped to highlight the reality of both harder and softer security challenges. The government can now proceed to draft a full official security strategy, to be laid before parliament possibly in 2015.